2018
DOI: 10.1111/pcn.12681
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy from a 6‐week double‐blind study and a 52‐week open‐label extension of aripiprazole in adolescents with schizophrenia in Japan

Abstract: These study results suggest that aripiprazole would be safe and well tolerated in both short- and long-term treatment for adolescents with SCZ in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…It is possible extended trials of oral Aripiprazole therapy could decrease the chance of non-adherence with the depot formula, as our study showed that those patients who stopped Aripiprazole Depot had taken Aripiprazole PO prior to Depot for a shorter time than those continuing. This might be because side effects continued to emerge weeks after the start of the treatment, [31][32][33] and as indicated by the present findings, patients experiencing side effects after receiving oral Aripiprazole are more likely to suffer from side effects with Aripiprazole Depot.…”
Section: Discussionmentioning
confidence: 67%
“…It is possible extended trials of oral Aripiprazole therapy could decrease the chance of non-adherence with the depot formula, as our study showed that those patients who stopped Aripiprazole Depot had taken Aripiprazole PO prior to Depot for a shorter time than those continuing. This might be because side effects continued to emerge weeks after the start of the treatment, [31][32][33] and as indicated by the present findings, patients experiencing side effects after receiving oral Aripiprazole are more likely to suffer from side effects with Aripiprazole Depot.…”
Section: Discussionmentioning
confidence: 67%
“…Three of the four studies with mortality rates of 0 were randomized controlled trials conducted in the presence of a physician, with the follow-up periods ≤ 2 years. 32 - 34 In two studies 33 , 34 the sample consisted of adolescents or recently hospitalized individuals. Thus, age of onset, disease severity, better compliance, and an insufficient period of time to observe deaths might explain this situation.…”
Section: Discussionmentioning
confidence: 99%
“…Aripiprazole showed efficacy in the treatment of adolescents with acute schizophrenia in several double-blind placebo-controlled studies, [8][9][10] leading to its approval for 13-to 17-year-old adolescents with schizophrenia. However, the LAI formulation still remains offlabel in youths.…”
Section: Introductionmentioning
confidence: 99%
“…This start regimen has the clear advantage of not requiring oral aripiprazole supplementation, eventually bypassing the potential issue of lack of adherence to oral treatment. Aripiprazole showed efficacy in the treatment of adolescents with acute schizophrenia in several double‐blind placebo‐controlled studies, 8 , 9 , 10 leading to its approval for 13‐ to 17‐year‐old adolescents with schizophrenia. However, the LAI formulation still remains off‐label in youths.…”
Section: Introductionmentioning
confidence: 99%